Imperial Executive, Cost of Governance and The Challenge of Development in Nigeria’s Fourth Republic - Abubakar Oladeji (Jurnal Administrasi Publik (Public Administration Journal), 2022)
There are raging debates about Nigeria's high cost of governance and its effects on socioeconomic development. Indeed, one of the talking points of the contemporary restructuring discourse is the need to drastically cut the cost of governance to allow more resources to fund the development of critical infrastructure. Understandably, the emphasis is always on the structure of governance of the executive presidential system and the bloated civil service. Indeed, much of the issue, however, is on the Executive, its imperial nature, its idiosyncrasies, and its style of governance. This paper assesses the features of the 'imperial executive' in Nigeria and the extent to which executive profligacy aggravates the cost of governance and hinders socioeconomic development. Using essentially secondary data, the paper found that the higher the recurrent expenditure, the more difficult it is to allocate adequate resources to capital expenditure in Nigeria. This scenario implies that a large chunk of public fund expenditure on the political elite makes it impossible to allocate adequate resources to other critical areas of development such as health, education, infrastructure etc. The paper suggests critical reforms in the structure of the executive presidential system as well as mechanisms to check the excesses and idiosyncrasies of the Executive in Nigeria.